Peran kualitas sistem informasi, fitur produk, dan kepuasan pengguna terhadap keputusan penggunaan Layanan Pegadaian Digital (PDS) di Pegadaian Semarang - Widianto, Fuad Hassan; Perdana, Tito Aditya; Farida, Ida; Kurniawan, Rudi (Nur Science Institute, 2025)
PT Pegadaian is currently transforming into a modern financial institution by launching a digital application designed to simplify customer transactions. This study examines the impact of information system quality, product features, and user satisfaction on the decision to utilize Pegadaian Digital Services (PDS) in the Semarang area. A quantitative approach was employed, using primary and secondary data sources. Primary data were obtained through questionnaires distributed to 100 customers and analyzed using multiple linear regression. The results show that information system quality, product features, and user satisfaction all have a significant positive effect on the decision to use PDS. Among these, user satisfaction proved to be the most influential factor. These findings underscore the importance for Pegadaian to continually enhance its digital services by improving system reliability, developing user-centric features, and increasing overall customer satisfaction. Strengthening these aspects is essential to encourage continued use of Pegadaian’s digital platform in an increasingly competitive financial service environment.